Designing a Project-Based Learning Digital Module for Entrepreneurship Education - febriati, farida; Nur, Miftahu; Aswan, Dedy; Bustanil Syah, Maenuddin (Cita konsultindo, 2025)
This research addresses the need for innovative and practical teaching materials in higher education entrepreneurship courses. The study aimed to develop and evaluate an interactive digital module based on Project-Based Learning (PjBL) to enhance student engagement and bridge the gap between theory and practice. Using a Research and Development (R&D) approach with the 3D model (Define, Design, Develop), a digital flipbook module was created, featuring multimedia content and QR codes that link theoretical concepts to practical project guidelines. The product was evaluated through expert validation and user practicality trials. The results demonstrated the module's high feasibility, achieving a content validity score of 86% and a media validity score of 94%. Furthermore, the module proved highly practical, with consistent scores from students (85-86%) and the course lecturer (90%). The study concludes that the systematic integration of a PjBL workflow into an interactive digital module is an effective solution for creating an active and autonomous learning environment. This research provides a valid, practical, and replicable model for developing modern educational resources. Future studies are recommended to quantitatively measure the module's impact on student learning outcomes and entrepreneurial competencies.